2005
DOI: 10.1163/156856805774406765
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of distracters in reflexive and memory-based localization

Abstract: We investigated the effects of spatial and temporal factors on manual localization of a visual target by measuring accuracy, precision, and bias. Spatial factors included manipulation of display as with or without distracters, with invariant or variant distracters, and with near or far distracters, respectively, in Experiments 1, 2, and 3. The target and distracters were of 1degrees dots differing only by luminance parameter; they were presented concurrently for 150 or 1000 ms while observers had to memorize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…One limitation of the two-process model is that it fails to predict whether a foveal or peripheral bias should occur in a given task, as the model focuses on absolute accuracy rather than bias. One proposal to account for biases is that the dissociation between the point of fixation and the locus of covert attention determines the direction of biases in spatial localization tasks, at least using perceptual reports (Uddin, 2006; Uddin et al, 2005a; Uddin, Kawabe, & Nakamizo, 2005b). According to this model, when fixation is maintained centrally and a peripheral target is presented, attention is focused at the point of fixation, resulting in a foveal bias in perceived location.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the two-process model is that it fails to predict whether a foveal or peripheral bias should occur in a given task, as the model focuses on absolute accuracy rather than bias. One proposal to account for biases is that the dissociation between the point of fixation and the locus of covert attention determines the direction of biases in spatial localization tasks, at least using perceptual reports (Uddin, 2006; Uddin et al, 2005a; Uddin, Kawabe, & Nakamizo, 2005b). According to this model, when fixation is maintained centrally and a peripheral target is presented, attention is focused at the point of fixation, resulting in a foveal bias in perceived location.…”
Section: Discussionmentioning
confidence: 99%
“…A bias of this kind would predict overestimation when the point of regard is below the target and underestimation when the point of regard is above the target. However, there are also investigators that have reported a foveal bias (e.g., Adam et al, 2008; Tsal & Bareket, 2005; Uddin, Kawabe, & Nakamizo, 2005). Biases of these kinds would predict underestimation when the point of regard is below the target and overestimation when the point of regard is above the target.…”
Section: Methodsmentioning
confidence: 99%